Transforming Grief into Power: Female Trauma and Agency in Netflix's Ballerina (2023) - Kirana Ramadhani (Jurnal Pendidikan Bahasa dan Sastra, 2026)
Contemporary South Korean cinema has increasingly reimagined female characters as active agents rather than passive victims of patriarchal violence. This study examines how the Netflix film Ballerina (2023), directed by Lee Chung-Hyun, represents female trauma and its transformation into empowerment through the feminist trauma theory of E. Ann Kaplan. Using a qualitative descriptive method grounded in close scene analysis, the study addresses two questions: how the film portrays female trauma in relation to patriarchal violence, and how it depicts the transformation of that trauma into female power and post-traumatic agency. Analysis of fourteen key scenes shows that trauma in Ballerina is first constructed through internalized suffering, mediated testimony, intrusive memory, psychological intimidation, and systemic sexual exploitation, before shifting into strategic investigation, reclaimed bodily agency, collective female solidarity, confrontation, and symbolic catharsis. Rather than treating grief as passive victimhood, the film reframes it as a transformative and political force that allows its protagonist, Ok-ju, to reclaim subjectivity within a patriarchal system, while resisting a fully redemptive closure. The findings extend feminist film scholarship on Korean cinema by positioning grief  rather than violence alone as a central analytic category for understanding female agency in contemporary transnational streaming media.